2020
DOI: 10.1111/1750-3841.15559
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower oil preservation by using chickpea flour film as bio‐packaging material

Abstract: The aim of this study was to evaluate the protective effect of biodegradable packages made with chickpea flour on the oxidation of sunflower oil. Chickpea flour films were prepared using the casting technique. To study the influence of storage time on films properties, the chickpea flour films were stored during 60 days at 25 °C and 52% relative humidity. In addition, sunflower oil samples were packaged in chickpea flour packages (CPs) and stored for 60 days at 25 °C. Lipid oxidation indicators were evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…The results of this study are consistent with the study carried out by Camiletti et al. (2021) in which chickpea‐based films were shown to protect sunflower oil from rancidity for a 2‐month storage period. In addition, previous studies about edible films and coatings added with antioxidant compounds demonstrated a preserving effect in the studied foods (Ganari et al., 2017).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The results of this study are consistent with the study carried out by Camiletti et al. (2021) in which chickpea‐based films were shown to protect sunflower oil from rancidity for a 2‐month storage period. In addition, previous studies about edible films and coatings added with antioxidant compounds demonstrated a preserving effect in the studied foods (Ganari et al., 2017).…”
Section: Resultssupporting
confidence: 92%
“…Chickpea flour was prepared following the methodology of Camiletti et al. (2021), without modifications. The chemical composition of the chickpea flour was 22.5 ± 0.39 g/100 g protein, 5.28 ± 0.41 g/100 g lipids, 2.87 ± 0.10 g/100 g ash, 10.44 ± 0.30 g/100 moisture, and 69.35 g/100 g total carbohydrates (Camiletti et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, edible films made from flours of natural blends of starch, protein, and lipids have been developed. These flours were elaborated from different crops such as chickpeas (Camiletti et al, 2021), peanuts (Riveros et al, 2018), triticale (Borneo et al, 2016), amaranth (Villamán Diéguez et al, 2015), and Babassu mesocarps (Maniglia et al, 2017). The films made from these flours exhibited good optical, barrier, and mechanical characteristics resulting from the combination among mechanical properties from starch, oxygen barrier properties from proteins, and capacity of lipids to block transport of moisture.…”
Section: Introductionmentioning
confidence: 99%